Challenges faced in Indonesia's naval modernisation - Basundoro, Alfin Febrian (2024)
Under the leadership of Defence Minister Prabowo Subianto, Indonesia has initiated a comprehensive naval modernisation programme. This programme involves procurements from various countries, including the United Kingdom, France, Italy, and Turkey. This programme presents challenges regarding training, ship maintenance, and ensuring technology transfers to support the local shipbuilding industry.